Univalent functions and Dirichlet-Morrey spaces. Issue 9 (2nd September 2021) - Tang, Shuan; Hu, Guangming; Shi, Qingtian; Jin, Jianjun
Abstract : This paper concerns univalent analytic functions f for which log ⁡ f ′ belong to Dirichlet-Morrey spaces. We establish some characterizations of Dirichlet-Morrey domains. Our results involve Schwarzian derivatives, quasiconformal extensions and Grunsky kernels of univalent functions.